PENGARUH LAYANAN INFORMASI BAKAT TERHADAP PEMAHAMAN BAKAT PESERTA DIDIK KELAS VIII MTSN - Pratiwi, Nurlita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractGuidance and counseling services that can help in understanding the talent of information services, therefore researchers want to know more about the Effect of Information Services About Talent Understanding Talent Students Class VIII MTsN 1 District Tanah Pinoh. The method used is descriptive method with the form of relationship studies. sample in this research is 56 students class VIII MTsN 1 District Tanah Pinoh. Technique of collecting data in this research is indirect communication technique. Data collection tool is a questionnaire. While the technique of data analysis using the formula percentage, product moment and continued with the coefficient of determination. Based on the results of data analysis showed that the information service about talent pesrta students class VIII MTsN 1 Tanah Pinoh District Melawi regency is in the range of